Binding kinetics of human ISWI chromatin-remodelers to DNA repair sites elucidate their target location mechanism - Erdel, Fabian; Rippe, Karsten (Nucleus, 2011)
Chromatin remodelers translocate nucleosomes along the DNA chain in an ATP-dependent manner. This catalytic activity is particularly important for DNA replication and repair since both processes require a significant amount of nucleosome translocations and assembly during DNA synthesis. Recently, we have studied the mobility and interactions of the human ISWI family chromatin remodelers Snf2H and Snf2L as well as Acf1, one of the non-catalytic subunits present in the ACF and CHRAC complexes of Snf2H. We proposed that these protein complexes identify their nucleosomal substrates via a continuous sampling mechanism. It rationalizes the relatively high nuclear mobility and abundance observed for all ISWI proteins in terms of fast target location. According to our model a certain type of ISWI complex visits a given nucleosome in the human genome on the timescale of several seconds to a few minutes. Here, we show that the ISWI proteins Snf2H, Snf2L as well as Acf1 accumulate at UV-induced DNA damage sites within seconds and reach a plateau after a few minutes. These findings corroborate the predictions of the continuous sampling mechanism as an efficient way for targeting chromatin remodelers to sites in the genome that require their activity. In comparison to the mobility of PCNA (proliferating cell nuclear antigen) that also accumulates at DNA repair sites the specifics of substrate location by chromatin remodelers are further characterized.